Pengaruh Penambahan Kitosan Terhadap Cemaran Mikrobiologis pada Abon Pindang Tongkol (Euthynnus affinis) - Purwaningtyas Kusumaningsih (Food Scientia : Journal of Food Science and Technology, 2022)
The processing of pindang tongkol becomes floss is a food technology to aim in extending the shelf life. The addition of chitosan inside the floss is to prevent the development of Vibrio sp., Proteus sp. and Pseudomonas sp. These bacteria live in high-salt environments such as brined mackerel product. The aim of this study was to examine the effect of chitosan to the quantity of Vibrio sp., Proteus sp. and Pseudomonas sp. in brined mackerel processing. In this study, were tested on samples of pindang tongkol, pindang floss without chitosan and pindang floss contains of 50 mg of chitosan. The total plate count (TPC) of pindang tongkol was reported to numerus to count (TNTC). TPC of floss without chitosan and floss contains chitosan, were less than 2.5 Ã— 102 colonies/ml (g). This value was qualify to the Indonesian National Standard (SNI) 7690.1:2013 and these result indicate that the processing of brined mackerel into floss and the addition of chitosan can reduce bacterial contamination. Identification of bacteria were using Thiosulfate Citrate Bile Salt Sucrose (TCBS) media, gram staining and API 20E kit. The bacteria from pindang tongkol was identified as Proteus vulgaris, while Pseudomonas luteola was from floss without chitosan. The addition of 50 mg of chitosan in floss was proven to prevent the development of halophilic bacteria such as Vibrio sp., Proteus sp., and Pseudomonas sp.